A Protocol for Fecal Microbiota Transplantation Using Freeze-Dried Capsules: Dosage and Outcomes in 171 Dogs with Chronic Enteropathy - Francesca Brugnoli; Barbara Simionati; Ilaria Patuzzi; Angiolella Lombardi; Maria Cecilia Giron; Edoardo Savarino; Sonia Facchin; Giada Innocente (Pets, 2025)
Background: In veterinary medicine, fecal microbiota transplantation (FMT) shows promise for treating chronic enteropathy (CE) in dogs, but standardized protocols for dosage, preparation, and administration are lacking. This study aimed to evaluate the efficacy of freeze-dried FMT capsules (cFMT) and to investigate the existence of a possible optimal dosage for dogs with CE. Methods: A multicenter prospective study was conducted on 171 dogs with CE, treated with freeze-dried FMT capsules (100 mg for dogs ≤ 10 kg, 200 mg for dogs > 10 kg). The dosage of freeze-dried FMT material was expressed in different ways, to investigate the effect of putative active principles. Clinical outcomes were assessed by classifying dogs as responders (R) or non-responders (NR) based on veterinary evaluations from a questionnaire, along with changes in the CIBDAI score and variations in 15 clinical signs of chronic enteropathy (CE). Data were collected before and 15 days after treatment. Results: Of the 111 dogs included in the final analysis, 82% showed a positive clinical response, with no significant differences in clinical response between capsule sizes or dosage, irrespective of how it was expressed. Conclusion: Effective dosage range for cFMT administration in dogs affected by CE was defined. The oral administration of 100 mg of freeze-dried cFMT daily for a month was shown to be sufficient to achieve an 80% response rate. Further studies are needed to explore additional factors that may influence the overall effectiveness of cFMT in treating CE.